2013
DOI: 10.1055/s-0033-1339876
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Basic Hexasubstituted Biguanides by Environmentally Friendly Methods

Abstract: A series of hexasubstituted biguanides was synthetized employing nonconventional and environmentally friendly methods. Their properties were studied computationally (basicity) and experimentally (basicity and catalytic properties in transesterification reaction).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…5 unable to determine due to similar solubilities of the diene and cycloadduct. 6 Approximately 40 % of the Achmatowicz-like product was also obtained as a product of oxidation. 7 Isolated after the washing with diethylether.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 unable to determine due to similar solubilities of the diene and cycloadduct. 6 Approximately 40 % of the Achmatowicz-like product was also obtained as a product of oxidation. 7 Isolated after the washing with diethylether.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our interest in guanidine-type of superbases [5,6], we were attracted by the paper of Calmes and coworkers who proved that cycloaddition could be a good approach toward chiral diamines [7]. They also suggested that such diamines could be excellent building blocks for synthesis of novel bifunctional catalysts or used as ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In recent time, important progress was made in the development of various solvent-free organic reactions [5], especially by the use of the ball milling technique [68]. In continuation of our interest in eco-friendly organic syntheses [914], we studied mechanochemical N -alkylation reactions of imides with alkyl halogenides, and the results are presented in this paper. Until now, ball milling N -alkylations of ureas [15], hydrazones [16], imines [1718], pyridines [19], pyrimidines [20], imidazoles [21], secondary amines [22], as well as allylic alkylation reactions [23] were reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…tri-, tetra-, and heptaguanide), [4] has not been followed by an equally successful development of synthetic methods in the field. While preparative chemistry of biguanides is well documented and spans from conventional procedures [6] to more environmentallyfriendly methods, [7] reports on the synthesis of higher analogues such as triguanides [8a] and tetraguanides still remain scarce with only a few examples found in the patent literature. [8b-f] Our group has recently made a contribution towards the synthesis, structure, and reactivity of pentasubstituted triguanide derivatives.…”
mentioning
confidence: 99%
“…[20] For this purpose, we followed a standard procedure and tested the benzyl triguanide derivative 4a in a transesterification reaction with methanol (see the Supplementary Material for details). Although the synthesized triguanides are predicted to be very strong bases, the catalytic activity of 4a in the transesterification reaction is lower than, for example N 1 ,N 2 -dicyclohexyl-N 4 ,N 4 ,N 5 ,N 5 -tetramethylbiguanide (DCTMB) or 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), [7] which are weaker bases (Fig. 3).…”
mentioning
confidence: 99%